Case Analysis of Public Procurement Management In Indonesia for The Period of 2023 - Hardinata, Dodi; Yenisrida, Yenisrida; Putra, Hendra Depriansyah (Dinasti Publisher, 2025)
This study aims to explain in detail the analysis of the problems of the implementation of government procurement of goods/services that occurred in Indonesia in the 2023 period. The procurement of government goods and services in Indonesia is a complex process and has a significant impact on the success of national development. This study also aims to analyze several procurement cases that occurred in 2023, as well as evaluate the effectiveness of policies, challenges faced, and opportunities for improvement in the procurement system in Indonesia. The research focuses on new policies, the application of technology in procurement, and issues such as transparency, efficiency, and accountability. Data is taken from various official government reports, articles, and interviews with related parties. The research method, used is a qualitative method, with a total of 105 informants. The results of the research, government procurement of goods and services in Indonesia in 2023 show some progress in terms of policies and technology, but still face major challenges related to transparency, accountability, and human resource competence. Technological capacity building and stricter law enforcement need to be done to realize more effective and efficient procurement. The update, in this study, is that providing recommendations for improvement based on the cases analyzed, the government needs to strengthen policies and the implementation of procurement that is more accountable and transparent. This can be done with several steps, including regular human resource training, holding regular training for government procurement personnel to improve their competence in understanding the latest procurement regulations and technology. Improving technology infrastructure, ensuring that information technology infrastructure throughout the region can support the implementation of SPSE and e-Catalog. Strict supervision and law enforcement, conducting stricter supervision of the procurement process and taking firm action against any form of irregularities to reduce the risk of corruption.